Inherited retinal dystrophies caused by RPE65 gene mutation: clinical presentation, economic and social burden - Jaśkowiak, Katarzyna; Stopa, Marcin; Krawczyński, Maciej; Niewada, Maciej; Golicki, Dominik (Klinika Oczna / Acta Ophthalmologica Polonica, 2022)
Inherited retinal dystrophies are a heterogeneous group of genetically determined disorders. The present paper discusses the role of mutation in the gene encoding the retinal pigment epithelium-specific protein RPE65 in the pathogenesis and course of dystrophies. Available epidemio-logical data are discussed with a focus on the clinical entities in which the RPE65 mutation is most typically identified, i.e. retinitis pigmentosa and Leber congenital amaurosis. As demonstrated by multiple studies, the lack of active retinal pigment epithelium-specific protein leads to near-total vision loss already in childhood or early adolescence. The paper addresses the issue of economic burdens associated with visual disturbances or vision loss resulting from progressive visual dysfunc-tion, including the burden on the healthcare system and public payer, and relating to the loss of productivity (indirect costs). In addition, an attempt has been made to evaluate the latter in the Polish reality. Unquantifiable costs, understood as referring to the loss of quality of life caused by progressive visual dysfunction, are discussed from the perspective of both patients and their caregivers.